Swim drink study: a randomised controlled trial of during-exercise rehydration and swimming performance. Issue 1 (25th October 2017) - Briars, Graham L; Gordon, Gillian Suzanne; Lawrence, Andrew; Turner, Andrew; Perry, Sharon; Pillbrow, Dan; Walston, Florence Einstein; Molyneux, Paul
Abstract : Objective: To determine whether during-exercise rehydration improves swimming performance and whether sports drink or water have differential effects on performance. Design: Randomised controlled multiple crossover trial. Setting: A UK competitive swimming club. Subjects: 19 club-level competitive swimmers, median age (range) 13 (11–17) years Interventions: Subjects were scheduled to drink ad libitum commercial isotonic sports drink (3.9 g sugars and 0.13 g salt per 100 mL) or water (three sessions each) or no drink (six sessions) in the course of twelve 75 min training sessions, each of which was followed by a 30 min test set of ten 100 m maximum-effort freestyle sprints each starting at 3 min intervals. Main outcome measure: Times for the middle 50 m of each sprint measured using electronic timing equipment in a Federation Internationale de Natation (FINA)-compliant six-lane 25 m competition swimming pool. Randomisation: Software-generated individual random session order in sealed envelopes. Analysis subset of eight sessions randomly selected by software after data collection completed. Masking: Participants blind to drink allocation until session start. Results: In the analysis data set of 1118 swims, there was no significant difference between swim times for drinking and not drinking nor between drinking water or a sports drink. Mean (SEM) 50 m time for no-drink swims was 38.077 (0.128) s and 38.105 (0.131) s for drink swims, p=0.701. Mean 50 m times were 38.031 (0.184) s for drinking sports drink and 38.182 (0.186) s for drinking water, p=0.073. Times after not drinking were 0.027 s faster than after drinking (95% CI 0.186 s faster to 0.113 s slower). Times after drinking sports drink were 0.151 s faster than after water (95% CI 0.309 s faster to 0.002 s slower). Mean (SEM) dehydration from exercise was 0.42 (0.11)%. Conclusions: Drinking water or sports drink over 105 min of sustained effort swimming training does not improve swimming performance. Trial registration: ISRCTN: 49860006.